Comparison of Alveolar Bone Loss in First Molars Based on Age and Sex: Study on Panoramic Radiographs - Farah Nabila Khoirunisa; Rini Widyaningrum; Silviana Farrah Diba; Rezmelia Sari (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: Alveolar bone loss (ABL) is a condition of osseous defect caused by periodontal disease or trauma from occlusion, cumulatively leading to weakening of the tooth-supporting structures and affecting tooth mobility. The first molars are among the most vulnerable teeth to ABL. Radiographically, alveolar bone loss occurs when the distance between the cementoenamel junction (CEJ) and the alveolar crest is more than 2 mm. This study aims to determine the differences in ABL between the first maxillary and mandibular molars on panoramic radiographs among various age and sex groups. Material and Methods: This analytical observational study utilized 100 digital panoramic radiographs from our dental hospital, which met the criteria and were grouped according to age: age group 1 (21-30 years), age group 2 (31-40 years), age group 3 (41-50 years), age group 4 (51-60 years), and age group 5 (>60 years). Each age group comprised 20 samples (10 males and 10 females). ABL measurements were carried out using Vatech's EzDent-I software. Results and Discussions: The mean ABL of first molars in the age group 1 to age group 5 were 0.03 ± 0.05 mm; 0.16±0.19mm; 0.35 ± 0.35 mm; 0.67 ± 0.46 mm; 1.00 ± 0.61 mm, respectively. The mean ABL of first molars in male and female groups were 0.45 ± 0.54 mm and 0.43 ± 0.50, respectively. The result of the Kruskal-Wallis test followed by the Mann-Whitney post hoc test showed a significant difference (p<0.05) in the ABL of first molars between all age groups, except the age group 4 with the age group 5. Meanwhile, the Mann-Whitney U test result reveals no significant difference in the ABL of first molars between males and females. Conclusion: Panoramic radiographs show a difference in the ABL of the first molars among age groups below 60-51. This difference is not influenced by sex.